2014
DOI: 10.1002/ajh.23629
|View full text |Cite
|
Sign up to set email alerts
|

Partial dysfunction of Treg activation in sickle cell disease

Abstract: Sickle cell disease (SCD) is a chronic inflammatory disease associated with multiple organ damage, chronic anemia, and infections. SCD patients have a high rate of alloimmunization against red blood cells (RBCs) following transfusion and may develop autoimmune diseases. Studies in mouse models have suggested that regulatory T cells (Treg) play a role in alloimmunization against RBC antigens. We characterized the phenotype and function of the Treg cell population in a homogeneous cohort of transfused SCD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 31 publications
4
50
2
1
Order By: Relevance
“…Other possible mediators of suppression may be CD4 + CD25 + FoxP3 + regulatory T cells (Tregs). Although the role of these cells in alloimmunization is not well understood [47, 48], it is known that such cellular component is able to recognize peptide/MHC complexes with greater avidity than the CD4 + CD25 - FoxP3 - T cells [49-51]. Thus, the assumption would be that HLA-DQ molecules present RBC epitopes recognized by T cells with relatively high avidity.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mediators of suppression may be CD4 + CD25 + FoxP3 + regulatory T cells (Tregs). Although the role of these cells in alloimmunization is not well understood [47, 48], it is known that such cellular component is able to recognize peptide/MHC complexes with greater avidity than the CD4 + CD25 - FoxP3 - T cells [49-51]. Thus, the assumption would be that HLA-DQ molecules present RBC epitopes recognized by T cells with relatively high avidity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of increased Treg numbers in the lung and HLN in naive SCD mice as well as the sharp increase in BAL Tregs in AAD SCD mice would seem to predict heightened capacity for regulation and disease suppression. However, there is some evidence that Tregs in SCD display an altered phenotype and may have reduced immunosuppressive capacity, although the latter remains debated 46,47 . Of particular note, alloimmunization associated with frequent blood transfusion, a mainstay of treatment of SCD, may produce dysfunction in both Tregs 46 and regulatory B cells (Bregs) 48 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Little is known about the role of CD4 + T cells in alloimmunization, 5 except for Treg cells. [6][7][8] Recently, we showed that the phenotype of CD4 + T cells from SCD patients differs according to whether M urine models of red blood cell transfusion show that inflammation associated with viruses or methylated DNA promotes red blood cell alloimmunization. In vaccination studies, the intensity of antigen-specific responses depends on the delay between antigen and adjuvant administration, with a short delay limiting immune responses.…”
Section: Introductionmentioning
confidence: 99%